Hepatocellular carcinoma - Global burden and risk factors - Blum, Hubert (Iatreia, 2007)
Global Burden. Hepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide and has been recently reviewed 1, 2. The incidence ranges from <10 cases per 100,000 population in North America and Western Europe as well as in Iran, Iraque and India to 50-150 cases per 100,000 population in parts of Africa and Asia (Fig. 1) where HCC is responsible for a large proportion of cancer deaths 3. However, a rise in the incidence of and mortality from HCC, most likely reflecting the increased prevalence of hepatitis C virus (HCV) infection, has recently been observed in most industrialized countries 4.